Methods of Explaining the Meaning of Words in Elementary Grades - qizi , Rajabova Xurshidabonu G’olib (Research Parks Publishers, 2023)
In this article, a scientific and theoretical analysis is made of the issue of understanding the meaning of words on the basis of educational dictionaries in primary-grade native language classes.